Reaction of coffee cultivars to Hemileia vastatrix Berk. & Broome strains in Venezuela, under controlled conditions - Ramírez, Emma; Rodríguez, Dorian; Hernández, Alexander (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Coffee rust resistance is of great importance in worldwide coffee crops, since its biotrophic pathogen shows, currently, more than 55 identified races with diverse virulent genes. This work was based on the determination of the reaction of five commercial coffee cultivars inoculated, under controlled conditions, with three strains of Hemileia vastatrix (race XXXIX and pathotypes Hv01ve and Hv02ve) previously identified in Venezuela. Three velvet leaves taken from six selected plants of five cultivars (Caturra, Catuai amarillo, Monteclaro, Colombia 27 y Castillo) were inoculated with 80 μL of a uredospore dilution (5 x 105 uredospores.mL-1), and incubated at 22 °C +/- 2 °C and 12 h light photoperiod. Incubation period, latency period, infection grade, number of initial lesions, number of sporulated lesions, area of lesion, and area of sporulated lesion were the variables used for evaluation. Results showed that number of initial lesion, number of sporulated lesion and area of sporulated lesion allowed to determine the presence of incomplete resistance in Castillo to race XXXIX, Castillo, Catuai and Colombia 27 to Hv01ve, and Monteclaro to Hv02ve, trials also showed possible complete resistance in Monteclaro to race XXXIX and Colombia 27 to Hv02ve. It is suggested that these results should be taken into account when selecting the coffee cultivars to be planted.